ANALISIS CLUSTER PENENTUAN PROMOSI PRODUK PASCA PANDEMI COVID 19 DENGAN METODE K MEANS - Devi Sugianti; Arief Soma Darmawan; Anas Syaifudin; Risqiati Risqiati (Universitas Methodist Indonesia, 2023)
The impact of the COVID-19 pandemic has been felt by all sectors, including the economic sector. UMKM have really felt the impact after the covid 19 pandemic with declining sales turnover. This study aims to classify products from UMKM that are not selling well and selling well. The K means method was chosen for grouping because it is simple and the K means method can group according to the same criteria grouped into a data cluster, for different data entered into another cluster. There are 28 data sets which will be grouped into 2 clusters . With the criteria of total goods sold, total transactions, difference in days and final stock. The data was taken from January 2022 to August 2022. After clustering, it was found that C1 had 12 products that were selling well, and for C2 there were 16 products that were not selling well. Therefore, UMKM can carry out sales promotion strategies that are fast and precise so that products that are not selling well can increase sales volume. Promotions can be carried out in the form of discounted promotions, mailer promotions, and fractional promotions.